The Influence of E-Learning and Emotional Intelligence on Psychological Intentions: Study of Stranded Pakistani Students - Alam, Fahad; Yang, Qing; Bhutto, Muhammad Yaseen; Akhtar, Nadeem (Frontiers in Psychology, 2021)
The COVID-19 pandemic has enforced the government to closed educational institutions around the world to control the infection of the disease, which is creating a significant impact on students’ academic activities. The unexpected shift from offline classes to online learning is creating a psychological disruption among the students. The primary aim of this research was to investigate the extent to which e-learning and emotional intelligence are associated with study stress, burnout, and performance among Pakistani students. The data were gathered on a sample of 387 students pursuing graduation and post-graduation from 10 different Chinese universities through a cross-sectional quantitative research design. The results revealed that both e-learning and emotional intelligence have significant effects on students’ perceived study-stress, burnout, and performance. These findings provided evidence that online classes and emotional intelligence can influence students’ study stress, burnout, and performance. The potential impact of emotional intelligence on the student’s psychological pressure has been explored.